Comparison of resting state functional networks in HIV infected and uninfected children at age 9 years - Stoltsz, Werner Heinrich (Division of Biomedical Engineering, 2019)
Over 2.5 million children are infected with HIV, the majority of whom reside in Sub-Saharan Africa. Treatment coverage is steadily gaining momentum, reducing mortality and morbidity. Yet little is known about brain development in HIV-infected (HIV+) children who are on highly-active antiretroviral therapy (ART), with viral load suppression from a young age. Here, we use resting state fMRI (rs-fMRI) to examine the impact of HIV and ART on the development of functional networks in 9-year-old vertically HIV-infected children compared to age-matched controls of similar socioeconomic status. We present analyses for a sample of 40 HIV+ (9.2 ± 0.20 years; 16 males) children from the Children with HIV Early Antiretroviral (CHER) clinical trial (Cotton et al. 2013; Violari et al. 2008) and 24 uninfected (12 exposed; 12 males; 9.6 ± 0.52 years) controls from an interlinking vaccine trial (Madhi et al. 2010). Scans were performed at the Cape Universities Body Imaging Centre (CUBIC) in Cape Town, South Africa. We investigated HIV-related differences in within- and between-network functional connectivity (FC) using independent component analysis(ICA) and seed-based correlation analysis (SCA). For SCA, seeds were placed in the structural core, in regions implicated in HIV-related between-group differences at age 7 years, and in regions associated with neuropsychological domains impaired in our cohort. In addition, we evaluated associations of past and present immune health measures with within-network connectivity using ICA. We found no HIV-related intra-network FC differences within any ICA-generated RSNs at age 9 years, perhaps as a result of within-network connectivity not being sufficiently robust at this age. We found a positive association of CD4%, both current and in infancy, with functional integration of left lobule 7 into the cerebellum network at age 9 years. Long-term impact of early immune health supports recently-revised policies of commencing ART immediately in HIV+ neonates. ii Compared to uninfected children, HIV+ children had increased FC to several seeds. Firstly, to seeds associated with the planning and visual perception neuropsychological domains. Secondly, to structural core seeds in the extrastriate visual cortex (of the medial visual network) and the right angular gyrus (of the temporoparietal network). Finally, to left paracentral (somatosensory network) and right precuneus (posterior DMN) seeds previously revealing between-group differences at age 7 years. The connections with greater FC in HIV+ children may variously indicate functional recruitment of additional brain capacity, immature excess of short-range connections, and/or immature excess of between-network connections. In conclusion, despite early ART and early virologic suppression, HIV+ children demonstrate instances of abnormal FC at age 9 years. Disruption to visual cortex is marked, consistent with indications from neuropsychological testing that visual perception is disrupted. The profile of HIV- and/or ART-related effects on FC differs considerably between the two ages of 7 and 9 years, but both show characteristics of immature functional organisation compared with age-matched controls.